Antibiotic Resistance of Salmonella enterica Serovar Typhi in Kolkata, India, and In Vitro Experiments on Effect of Combined Chemotherapy - Shyamapada Mandal; Manisha DebMandal; Nishith Kumar Pal (The Scientific World Journal)
This communication states the changing patterns of Salmonella enterica serovar Typhi (S. Typhi) isolates causing enteric fever in and around Kolkata, India. Among the isolates resistance to ampicillin (A), chloramphenicol (C), cotrimoxazole (Co) and tetracycline (T) were plasmid mediated; the plasmid was unstable in S. Typhi, and the other enteric bacteria like Escherichia coli, Klebsiella pneumoniae and Proteus vulgaris were found to be the potential source of dissemination of such plasmids into S. Typhi. The infection with such S. Typhi strains were successfully treated with ciprofloxacin (Cp: MICs 0.0075–0.075 μg mL−1) and/or ofloxacin (Ofx: MICs 0.0125–0.075 μg mL−1), but in the later course, the S. Typhi strains, showing resistance to nalidixic acid, developed low level of resistance to Cp and Ofx, causing the treatment failure. Thus, the treatment regimen was shifted to the third generation cephalosporins like ceftriaxone (Ct) and cefotaxime (Cf). Keeping in mind the anticipation of development of resistance to Ct/Cf, we prepared the treatment regimen for MDR enteric fever, based on the double-drug synergy tests in vitro; Cp-gentamycin (FICI 0.121–0.216) and Cp-trimethoprim (FICI 0.14–0.483) combinations were found effective against S. Typhi isolates having decreased sensitivity to cp (MICs: 0.5–1.25 μg mL−1).